Implementation of Indonesian Flag for Electricity Standards on Non-Conventional Vessel at Palipi Harbor - Tona, Tasdik; Nurwahidah, Nurwahidah (Department of Naval Architecture - Diponegoro University, 2024)
This research aims to analyze the current level of application of electricity standards on Indonesian-flagged non-convention ships by Gross Tonnage (GT 7-35), identify the obstacles faced in implementing electricity standards on Indonesian-flag non-convention ships by Gross Tonnage (GT 7-35) and how to make efforts in increasing the application of electrical standards on Indonesian-flagged non-convention ships by Gross Tonnage (GT 7-35). The research method used is a qualitative method with data collection techniques involving observation, documentation, and interviews with related parties. The data analysis technique used is qualitative descriptive analysis. The results show that the electrical condition of non-convention ships varies greatly depending on factors such as ship type, ship size, and the level of maintenance performed. The constraints faced in the implementation of electrical standards on Indonesian-flagged non-convention ships by Gross Tonnage (GT 7-35) are limited resources, understanding and awareness, changes in technology and regulations, and lack of routine maintenance and inspections; and collaboration between authorities, ship owners, and ship crews has not been maximized in the implementation of electrical standards, as well as the absence of training programs or resources offered by related parties to improve understanding and skills related to ship electricity.